Implementation Of Edutainment Methods In Developing 21st Century Skills In Elementary Schools - Jesica Dwi Rahmayanti, Jesica Dwi Rahmayanti; Nadlir, Nadlir (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2024)
The aim of the research is to describe the application of edutainment methods at Muhammadiyah 16 Surabaya Elementary School in developing 21st century skills in elementary schools. This research is qualitative research that uses a case study approach. The data analysis used is the Miles and Huberman model combined with data triangulation. The research results show that the application of the edutainment method in developing 21st century skills is carried out through several techniques, namely games, role playing, demonstrations, storytelling with music/singing, field trips, final project projects. Apart from that, it is also realized in various school activity programs, such as outdoor learning, guest teacher, outbound activity, character camp, assembly learning, entrepreneur week, creative festival and final assignment projects. Edutainment has a good impact on student development, namely it can motivate students to master critical thinking and problem solving skills, creative, communicative, collaborative skills, honest, independent, responsible, religious and disciplined. The obstacles to implementing edutainment methods include lack of support and assistance from parents, limited time and energy from educators, lack of time to deliver learning material, not all teachers are able to present interesting lessons, and have storytelling or music skills.